2021
DOI: 10.3390/molecules26082315
|View full text |Cite
|
Sign up to set email alerts
|

Plant Occurring Flavonoids as Modulators of the Aryl Hydrocarbon Receptor

Abstract: The aryl hydrocarbon receptor (AhR) is a transcription factor deeply implicated in health and diseases. Historically identified as a sensor of xenobiotics and mainly toxic substances, AhR has recently become an emerging pharmacological target in cancer, immunology, inflammatory conditions, and aging. Multiple AhR ligands are recognized, with plant occurring flavonoids being the largest group of natural ligands of AhR in the human diet. The biological implications of the modulatory effects of flavonoids on AhR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 153 publications
0
41
0
1
Order By: Relevance
“…The balance between Tregs and effector T cells reflects the immune homeostasis [ 61 ]. A previous study reported that quercetin and other flavonoids could modulate the aryl hydrocarbon receptor (Ahr), which further influenced Tregs' activation via Foxp3, the main transcription factor for Tregs [ [62] , [63] , [64] ]. On the other hand, the activation of heme oxygenase-1 (HO1) via the Nrf2/HO-1 signaling pathway is reported to increase Foxp3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The balance between Tregs and effector T cells reflects the immune homeostasis [ 61 ]. A previous study reported that quercetin and other flavonoids could modulate the aryl hydrocarbon receptor (Ahr), which further influenced Tregs' activation via Foxp3, the main transcription factor for Tregs [ [62] , [63] , [64] ]. On the other hand, the activation of heme oxygenase-1 (HO1) via the Nrf2/HO-1 signaling pathway is reported to increase Foxp3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is known that testicular functions (i.e., spermatogenesis and sperm motility), and hence male fertility, are affected by activation of AHR induced by environmental toxicants [223]. Therefore, AhR has been studied as an interesting target of pollutant-induced cancers and, specifically, natural products, among which flavonoids, have seized the attention of the scientific community in these regards [224]. In particular, the isoflavone genistein from soy was showed to hamper TCDD-dependent downregulation and methylation of BRCA-1, whose alteration is known to play a pivotal role in the onset of breast cancer, along with decreasing levels of DNMT-1 and cyclin D1 in MCF-7 cells, proving the role of genistein in counteracting ER (estrogen receptor) α-positive breast cancer cells via antagonizing AhR [225].…”
Section: Dioxinsmentioning
confidence: 99%
“…Plant flavonoids are polyphenolic chemicals obtained mostly from vegetables, nuts, seeds, and fruits that are important components of green tea and cocoa-based beverages. Flavonoids have been proven to show anticancer effects through a variety of mechanisms, including anti-oxidation, inactivation of carcinogen, apoptosis induction, angiogenesis inhibition, and alterations of multidrug resistance (Goya-Jorge et al 2021 ; Kapoor et al 2021 ). Consumption of flavonoids has been demonstrated to have cardiovascular and antithrombotic therapeutic benefits due to antiplatelet action.…”
Section: Flavonoidsmentioning
confidence: 99%